2017
DOI: 10.1128/genomea.00906-17
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Draft Genome Sequences for Four Drug-Resistant or Outbreak-Associated Shigella sonnei Strains Generated with PacBio Sequencing and Whole-Genome Maps

Abstract: Drug-resistant Shigella sonnei poses a clinical and public health challenge. We report here the high-quality draft whole-genome sequences of four outbreak-associated S. sonnei isolates; three were resistant to two or more antibiotics, and one was resistant to streptomycin only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Pacific BioSciences sequencing was completed as previously described (Lindsey et al, 2017). Briefly, E. coli genomic DNA was extracted according to the manufacturer's protocol (Archive Pure, 5 Prime, Gaithersburg, MD).…”
Section: Sequencingmentioning
confidence: 99%
“…Pacific BioSciences sequencing was completed as previously described (Lindsey et al, 2017). Briefly, E. coli genomic DNA was extracted according to the manufacturer's protocol (Archive Pure, 5 Prime, Gaithersburg, MD).…”
Section: Sequencingmentioning
confidence: 99%
“…A trimethoprim/sulfamethoxazole-resistant Shigella isolate was first reported in Japan [ 19 , 20 ], followed by the emergence of diverse resistant Shigella types [ 21 , 22 ]. Previous studies reported a frequent resistance to some of the commonly used antibiotics, such as ampicillin and tetracyclines, worldwide [ 23 25 ]. Recently, the resistance to quinolones and cephalosporins was reported as well [ 12 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…We proceeded to validate our predictions experimentally by evaluating growth requirements of the predicted auxotrophs. We were able to obtain six E. coli (61)(62)(63)(64), three Yersinia (65), three Salmonella (66,67), three Shigella (68,69), and one Klebsiella (70) strain (Fig. 6).…”
Section: Experimental Validation Of Auxotrophies Highlight Technologicalmentioning
confidence: 99%